Association of leptin gene DNA methylation with diagnosis and treatment outcome of anorexia nervosa - Neyazi, Alexandra; Herzog, Wolfgang (Frontiers in psychiatry, 2019)
Epigenetic alterations are increasingly implicated in the pathophysiology of anorexia nervosa (AN) but are as yet poorly understood. We investigated possible associations between the leptin gene (LEP) and the leptin receptor gene (LEPR) DNA promoter methylation and (1) a diagnosis of AN and (2) outcome after a 10 months psychotherapeutic outpatient treatment. 129 (LEPR: n=135) patients with AN were investigated during the large scale psychotherapeutic Anorexia Nervosa Treatment Outpatient Study (ANTOP) trial, compared to 117 (LEPR: n=119) age and height matched, normal-weight healthy controls. Blood samples were taken at baseline, the end of therapy (40 weeks) and the 12-months follow-up and compared to controls. Methylation was measured in whole blood via bisulfite sequencing. Within the promoter region 32 (LEP) and 39 CpG sites (LEPR) were analysed. Two key findings were observed. First, LEP and LEPR methylation at baseline were lower in patients compared to controls (LEP: [%] AN: 30.94 ± 13.2 vs. controls: 34.53 ± 14.6; LEPR ([%] AN: 3.73 ± 5.4 vs. controls: 5.22 ± 8.3, mixed linear models: both P<0.001). Second, lower DNA methylation of the LEP promoter, with a dynamic upregulation during treatment, was associated with a full recovery in AN patients (% change from baseline to follow-up in full recovery patients: +35.13% (SD: 47.56); mixed linear model: P<0.0001). To test for potential predictive properties of mean LEP DNA methylation a LEP DNA methylation cut-off (31.25% DNA methylation) was calculated, which significantly discriminated full recovery vs. full syndrome AN patients. This cut-off was then tested in a group of previously unclassified patients (missing follow-up data of the Structured Interview for Anorexic and Bulimic disorders; n=33). Patients below the cut-off (31.25% LEP DNA methylation) showed an increase in BMI over time, while those above the cut-off had a decrease in BMI (ANOVA at the 12-months follow-up: P = 0.0142). To our knowledge, this is the first study investigating epigenetic alterations in AN over time. Our findings indicate that LEP DNA methylation might be involved in the disease course of AN.
Gesehen am 22.05.2019